2009
DOI: 10.3354/dao02002
|View full text |Cite
|
Sign up to set email alerts
|

Renibacterium salmoninarum p57 antigenic variation is restricted in geographic distribution and correlated with genomic markers

Abstract: The 57 kDa protein (p57) is an important diagnostic antigen that is implicated in the pathogenesis of salmonid bacterial kidney disease. Little is known about the nature and extent of antigenic variation in p57. Previously, we reported that p57 produced by Renibacterium salmoninarum Strain 684 contains a mutation that disrupts monoclonal antibody (MAb) 4C11 binding. In the present study, we examined MAb binding to a panel of 23 additional R. salmoninarum isolates obtained from diverse geographic locations to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This variation could be associated with differences in the major antigen p57 protein (Wiens et al . ; Wiens & Dale ).…”
Section: Renibacterium Salmoninarummentioning
confidence: 99%
See 3 more Smart Citations
“…This variation could be associated with differences in the major antigen p57 protein (Wiens et al . ; Wiens & Dale ).…”
Section: Renibacterium Salmoninarummentioning
confidence: 99%
“…). Interestingly Wiens and Dale () suggested that some recombination must occur, at least between genes of the major soluble antigen (MSA) (a single Ala139 to Glu mutation in both genes). When these authors analysed R. salmoninarum isolated from Norway, 5 of the 8 contained this sequence variation overlapped at the same geographical area.…”
Section: Renibacterium Salmoninarummentioning
confidence: 99%
See 2 more Smart Citations
“…salmoninarum is a facultative intracellular pathogen and several virulence factors have been identified [12]. P57 (57-kDa protein) is the best studied among these virulence factors and plays a significant role in cell agglutination and immune-suppression of the host [14][15][16][17]. Fish infected with R. salmoninarum can display external and internal clinical signs such as exophthalmia, blebs and blister on the epidermis with white or yellowish haemorrhagic fluid, petechiae and haemorrhages around the fins and lateral line, swelling of the kidney, heart, spleen, and liver alongside creamy-white and greyish granulomatous lesions on the surface of the viscera [18][19][20].…”
Section: Introductionmentioning
confidence: 99%